Falta de aplicación del principio de celeridad en los delitos de Violencia Psicológica contra la mujer o miembros del núcleo familiar - León López, Katheryn Daniela (2024)
This Curricular Integration Work is titled: “Lack of application of the principle of speed in crimes of Psychological Violence against women or members of the family nucleus” and seeks to investigate the lack of this procedural principle in crimes of Psychological Violence, which This is evidenced by the fact that there are no convictions for these processes. The principle of speed, fundamental in the administration of justice, establishes the obligation to process cases quickly and efficiently, thus guaranteeing the protection of the rights of victims and the prompt resolution of conflicts. However, in crimes of Psychological Violence, a tendency to delay is detected in the processing of judicial processes, which results in an unnecessary prolongation of the suffering of the victims and possible impunity for the aggressors. In this Curricular Integration Work, the use and application of materials and methods that allowed its development were made. For this purpose, surveys and interviews were carried out with legal professionals, the results of which served to propose the development of a reform project to the COIP. With the purpose of contributing to the strengthening of the action of the judicial system against Psychological Violence, highlighting the relevance of streamlining legal procedures to safeguard the rights of victims and avoid situations of impunity.